Increasing Arctic Tundra Flooding Threatens Wildlife Habitat and Survival: Impacts on the Critically Endangered Siberian Crane (Grus leucogeranus) - Haverkamp, Paul J.; Bysykatova-Harmey, Inga; Germogenov, Nikolai; Schaepman-Strub, Gabriela (Frontiers in Conservation Science, 2022)
Climate change is causing Arctic temperatures to increase at least twice as fast as the planet on average. Temperature and precipitation are predicted to continue increasing, such that flooding might become more prevalent in the new Arctic. Increased flooding frequency and extreme flooding events may pose new threats to Arctic biodiversity through habitat disturbance and decreased survival. We used the Siberian crane (Grus leucogeranus) as a model organism to investigate how flooding influences nesting habitat availability and juvenile counts. When spring flooding destroys eggs, adults either do not raise any chicks or have reduced time to prepare them for their long migration to China, thus years with extensive flooding could negatively impact future crane generations. We used nest site observation data from 14 surveys between 1995-2019, habitat mapping based on Landsat 8 imagery, and species distribution modeling to predict Siberian crane potential nesting habitat. Nesting habitat loss due to extreme flooding was calculated by overlaying this potential nesting habitat with Global Surface Water data. The percent of potential flooded nest sites varied between 6.7-55% across years, with a significant increase between 2001 and 2018. Extreme flood events, as experienced in 2017 and 2018, eliminated almost half of the potential nesting habitat. Importantly, we found that the percentage of flooded nest sites across years was negatively correlated with the number of observed juveniles. The Arctic lowlands are exposed to seasonal water level fluctuations that species have evolved with and adapted to. Siberian cranes and other species depending on Arctic ecosystems are expected to continue adapting to changing flood conditions, but extreme flood events further threaten the long-term survival of critically endangered species. It is imperative to assess how ecosystems and species respond to climatic extremes to support Arctic conservation strategies.